2004
DOI: 10.1017/s0031182004006092
|View full text |Cite
|
Sign up to set email alerts
|

The amphidial neuron pair ALD controls the temperature-sensitive choice of alternative developmental pathways in the parasitic nematode, Strongyloides stercoralis

Abstract: The parasitic nematode Strongyloides stercoralis, has several alternative developmental pathways. Upon exiting the host (humans, other primates and dogs) in faeces, 1st-stage larvae (L1) can enter the direct pathway, in which they moult twice to reach the infective 3rd-stage. Alternatively, if they enter the indirect pathway, they moult 4 times and become free-living adults. The choice of route depends, in part, on environmental cues. In this investigation it was shown that at temperatures below 34 degrees C t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 21 publications
0
32
0
Order By: Relevance
“…C. elegans gpa-3 is expressed in eight pairs of chemosensory neurons in the amphidial complex (ADF, ADL, ASE, ASG, ASH, ASI, ASJ and ASK), two pairs of sensory neurons in the phasmids (PHA and PHB) and two other non-sensory cells (Jansen, et al, 1999). The amphidial neurons of S. stercoralis have been described and their homologies with amphidial neurons of C. elegans have been proposed based on morphology, position of cell bodies within the lateral ganglion and, in several cases, function inferred from microlaser ablation studies (Ashton, et al, 1995;Ashton, et al, 1998;Lopez, et al, 2000;Nolan, et al, 2004;Ashton, et al, 2007). We have not yet determined the specific identities of the GFP-expressing neurons in S. stercoralis transformed with pAJ09.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C. elegans gpa-3 is expressed in eight pairs of chemosensory neurons in the amphidial complex (ADF, ADL, ASE, ASG, ASH, ASI, ASJ and ASK), two pairs of sensory neurons in the phasmids (PHA and PHB) and two other non-sensory cells (Jansen, et al, 1999). The amphidial neurons of S. stercoralis have been described and their homologies with amphidial neurons of C. elegans have been proposed based on morphology, position of cell bodies within the lateral ganglion and, in several cases, function inferred from microlaser ablation studies (Ashton, et al, 1995;Ashton, et al, 1998;Lopez, et al, 2000;Nolan, et al, 2004;Ashton, et al, 2007). We have not yet determined the specific identities of the GFP-expressing neurons in S. stercoralis transformed with pAJ09.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, transformation constructs that are expressed in such small, defined groupings of cells in S. stercoralis may provide the basis for genetically targeted cell ablation using modified channel forming proteins as described for C. elegans (Driscoll and Chalfie, 1991;Harbinder, et al, 1997). In some instances such an approach could provide an alternative to microlaser surgical techniques currently in use for S. stercoralis (Lopez, et al, 2000;Nolan, et al, 2004;Ashton, et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis has been bolstered by the discovery that dauer switching in C. elegans and the switch between homogonic and heterogonic developmental alternatives in the parasitic nematode Strongyloides stercoralis are controlled by the homologous amphidial neurons (Bargmann and Horvitz, 1991;Ashton et al, 1998;Nolan et al, 2004). Our laboratory is investigating possible parallels between molecular mechanisms regulating dauer development in C. elegans and the development of L3i in S. stercoralis.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 However, more recent research has found that in temperatures below 34°C, larvae molt four times and develop into free-living sexually mature adults, and in temperatures above 34°C, larvae molt twice and develop into infective filariform larvae. 15,16 Chemosensory factors may also influence larval differentiation. Chemosensory and thermosensory neurons are contained in the amphids in nematodes.…”
Section: Strongyloides' Life Cyclementioning
confidence: 99%